Walls That Speak: Creative Multivocality Within Tangatarua - Thyne, Debbi (Auckland University of Technology, 2009)
This research posits art as an encounter, an encounter between the conceptual worlds of artists and of viewers. It acclaims the respective art skills within the marae (communal meeting place) named Tangatarua at Waiariki Institute of Technology, Rotorua. Tangatarua Marae is a place of bicultural encounter. This writing includes readers in the social relations of this encounter. This is a qualitative study that uses an interpretive epistemology to examine some of the art forms of Tangatarua. My focus is on micronarratives - that is, on intimate, improvised meanings generated by some of the small artworks. These reference and affirm the symbolism of the carvings but are less visible due to their lesser scale and interstitial placement within the interior architecture. They are rendered more visible through the phenomenological detail of participant accounts as well as the positivism of a formalist critique. I posit art as a dialogical activity, inseparable from the phenomenological conditions that precede and inform it, and inseparable from the emergent meaning that is forged at its encounter. I contend that the collaborative mode of art production within Tangatarua embodies this dialogical model. I amplify some of the tangible art forms of Tangatarua by dismantling the intangible discursive forms that have impinged on them. These include aspects of the political context of the establishment of the marae, Waiariki Institute of Technology’s bicultural framework, and the pedagogy of its Art School. My writing is underpinned by a participatory paradigm acknowledging my situatedness as an artist participant within Tangatarua, a woman of Ngai Tahu descent, and art tutor at Waiariki Institute of Technology. This study similarly acknowledges the multifaceted, experiential transactions between those artists whose small collective gestures have informed and transformed the interior of Tangatarua.
Keywords: Bicultural art; Relational aesthetics; Art pedagogy; Dialogical meaning